Life Cycle Inventory (LCI) Process of The Rare Earth Elements (Rees) Based on Exploitation of Secondary Sources: New Kankberg Gold Mine, Sweden Case Study - Boguslaw BIEDA; Dariusz SALA (Communications of International Proceedings, 2021)
The goal of this paper is to describe the life Cycle Inventory (LCI) approach to the Rare Earth Elements (REEs) recovery from secondary sources, derived from the New Kankberg (Sweden) flotation tailings case study, considering uncertainty. The presented LCI study was conducted as the part of the project „ENVIREE - Eenvironmentally friendly and efficient methods for extraction of REEs from secondary sources”, based on the data from ENVIREE ERA-NET ERA-MIN-funded research project. The functional unit (FU) has been defined as 1000 kg of a secondary source (flotation tailings - input material) for both case studies. Life cycle system boundaries, represent a gate-to-gate perspective, include excavation and transport of secondary sources as well as beneficiation/pre-treatment with disposal and land reclamation of the residues after beneficiation. The system boundaries for this study do not include leaching or separation processes. The flotation tailings from the operating New Kankberg gold mine is sent to re-processing /beneficiation for REE recovery, instead of being sent to the tailing pond. For the production of 10 kg of concentrate in the beneficiation step (after flotation + mag separation processes) have been used 1000 kg of tailing. The residues after beneficiation, equivalent to 990 kg, are sent to the tailing pond to be disposed and reclaimed. From the process of production of REEs there are emissions to air, water and ground reported in scientific literature. Because of the lack information available on-air emissions from the beneficiation of New Kankberg tailings pilot operation, we neglected these emissions. LCI study and obtained data will be available for the the final LCA analysis where the collected data is analyzed in the context of methodology, scope and study goals and where the quality of study outcomes is assessed.
Keywords: Rare Earth Elements (REEs); Life cycle inventory (LCI); Life cycle assessment (LCA); secondary sources; flotation; beneficiation.